Decolorization and degradation of methylene blue by photo-Fenton reaction under visible light using an iron-rich clay as catalyst: CCD-RSM design and LC-MS technique - Zimmermann, Bárbara Machado; Peres, Enrique Chaves; Dotto, Guilherme Luiz; Foletto, Edson Luiz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In this work, an iron-rich bentonite was thermally modified at 200 oC and posteriorly used as a heterogeneous catalyst in the decolorization and degradation of methylene blue dye (MB) by photo-Fenton reaction under visible irradiation. The variables such as catalyst concentration and pH were investigated in the reaction system to detect the optimal decolorization conditions using the response surface methodology (RSM) coupled with Central Composite Design (CCD). Photodegradation of MB was analyzed by LC-MS technique. The results indicated that the optimal conditions to obtain 94% of MB decolorization efficiency were pH = 2.4 and catalyst mass = 0.02 g. It was also possible to verify that the simultaneous combination of catalyst, hydrogen peroxide and visible light in the reaction medium was primordial for the increasing MB decolorization efficiency. MB degradation occurred partially at 180 min of photo-Fenton reaction, since the presence of dye in the solution was reduced, leading to its transformation into different intermediate products. Therefore, the catalyst used in this work has demonstrated a great potential for the degradation of cationic dye, allowing its use in advanced oxidation processes